KUALITAS AIR DAN PERSEPSI PENGUNJUNG DI KAWASAN WISATA SUNGAI SAMPUREN PUTIH KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA Water Quality and Visitor Perception in The Area of The White River Tourism Sampuren Deli Serdang District of North Sumatera Provin - Ivan Sinaga; Pindi Patana; Rusdi Leidonald (AQUACOASTMARINE, 2017)
Natural potential is the main attraction in the tourist activity, including the physical nature, fauna and flora. The existence of Sungai Sampuren Putih region is widely known as one of the tourist destinations in the District of Sibolangit Deli Serdang, North Sumatra. The purpose of this study was to determine the effect of water quality on the level of visits and tourism potential of the river as well as assess the perceptions of visitors and the management of the activities of Sungai Sampuren Putih. This study was conducted over three months are May to July 2016. Data analysis using Water Quality Parameters and questionnaire. Sungai Sampuren Putih water quality through water chemistry to measure physical parameters Sampuren River White stated that I belong lightly polluted station that is 1.92 while the station II and III stations classified as good, namely 0.83 and 0.72. Value 90% comfort level visitors expressed comfortable. Judging of the appeal because the rocks 65,06%. White Sampuren river has good tourism potential, it can be seen from the results of interviews and questionnaires.Keywords: Water Quality, Traffic People, River Tourism Zone, Deli Serdang